2017
DOI: 10.1007/s00417-017-3603-3
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of ocular cicatricial pemphigoid: a retrospective cohort study

Abstract: These retrospective data suggest that RTX is efficacious and well tolerated when included for the treatment of OCP. Controlled studies are necessary to identify the role of this IMT agent in the therapeutic arsenal, especially its optimum dose and duration of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
0
20
2
2
Order By: Relevance
“…In order to assess the correlation between the MMP‐involved site and the response to RTX, we conducted a review of the literature. Using the search terms ‘MMP’ and ‘rituximab’ in the PubMed database, we found 30 articles 5–34 (detailed in Table ) covering 167 patients with MMP treated with RTX. Their demographic and therapeutic characteristics are shown in the supplementary material (Tables and , respectively).…”
Section: Reportmentioning
confidence: 99%
“…In order to assess the correlation between the MMP‐involved site and the response to RTX, we conducted a review of the literature. Using the search terms ‘MMP’ and ‘rituximab’ in the PubMed database, we found 30 articles 5–34 (detailed in Table ) covering 167 patients with MMP treated with RTX. Their demographic and therapeutic characteristics are shown in the supplementary material (Tables and , respectively).…”
Section: Reportmentioning
confidence: 99%
“…In a retrospective cohort, mucous membrane pemphigoid ( n = 14) exhibited disease control in 85.7% (partial response: 64.3%, complete response: 28.6%) (67). Similarly, some encouraging data have been obtained in ocular cicatricial pemphigoid (68). A meta-analysis showed that rituximab is also a promising option in epidermolysis bullosa acquisita (69).…”
Section: Bullous Disorders: Bullous Pemphigoid (Bp) and Other Bullousmentioning
confidence: 83%
“…The progression of ocular involvement was controlled and no cicatrization developed in the follow-up. Adverse effects were mild and transient [111].…”
Section: Therapy Of Mucous Membrane Pemphigoid (Cicatricial Pemphigoid)mentioning
confidence: 94%